Peningkatan Kemampuan Kognitif Melalui Metode Bermain Mencampur Warna Pada Anak TK Barunawati Tanjungpinang - Supatmi Supatmi; Wasiah Wasiah; Yuni Resiyati (LPPI Yayasan Almahmudi bin Dahlan, 2023)
This study is motivated by the low ability of cognitive development aspects of recognizing colors in kindergarten children Barunawati Tanjungpinang. One solution to overcome this problem is to use the method of playing mixing colors. The purpose of this study was to describe the improvement of cognitive abilities of the ability to recognize colors through the method of playing mixing colors in kindergarten children Barunawati Tanjungpinang. This research method is Classroom Action Research (PTK) conducted in two (2) cycles, each cycle consists of 3 meetings with four stages namely planning, implementation, observation and reflection. The research time was from April to May 2022. The subjects in this study were Barunawati Tanjungpinang Kindergarten children consisting of 14 children, namely: 8 boys and 6 girls. The data collection technique in this study is through observation (observation) and documentation of activities. The conclusion of this study is that the ability to recognize the colors of Barunawati Tanjungpinang Kindergarten children has an average percentage in cycle I of 39.29%. In cycle II the ability to recognize children's colors increased by 62.98%. From the results of overall data analysis from pre-action to cycle II, it can be seen that the increase in children's ability to recognize colors obtained an average value of 79.94%. Thus it can be concluded that the method of playing mixing colors can improve the cognitive ability to recognize the colors of children at Barunawati Tanjungpinang Kindergarten. Keywords: Cognitive Ability, Knowing Colors, Playing Mixing Colors.